Mammary gland cancer. Relationship between estrogen receptors and stage of disease - Garófalo, Elsa G; Martino, Idivia; Sabini, Graciela; Peluffo, Jorge (Cirugía del Uruguay, 1984)
Widely recognized is the importance of the determination of estrogen receptors (ER) in mammary gland cancer as a parameter of therapeutic orientation and prospective evolution of this disease.